Oral health and quality of life among people with severe or long-term mental illness: A call for interprofessional collaboration - Bjørkvik Jofrid; Quintero Diana Patricia; Jensen Karsten Hogh M; Virtanen Jorma I (United Kingdom, 2022)
People with severe or long-term mental illness (SMI) have poorer oral health than the general population has, but little is known about how, to what extent, and in what ways oral health problems affect daily functioning, quality of life and well-being among people in this patient group. The present study investigated oral health and oral health-related quality of life for persons with SMI in Norway. The longitudinal clinical study targeted SMI patients with their age- and gender-matched control patients at a public dental clinic in Norway. SMI patients were recruited from an ambulatory team within community mental health services. Clinical examinations followed the WHO criteria. We used a validated Oral Impact on Daily Performance (OIDP) instrument to assess oral health-related quality of life (OHRQoL). The prevalence of oral impact (OIDP > 0) was 77% among SMI patients and 22% among the controls. More than 60% of the SMI patients reported difficulties showing their teeth without embarrassment, compared to 5.5% of the controls. The results suggest that shame is a key factor inhibiting patients faced with the need for dental treatment. Collaboration between dental and mental health professionals is therefore essential for this patient group to enjoy dignified oral health and quality of life.